2017
DOI: 10.1007/s00270-017-1792-0
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Percutaneous Portal Vein Intervention in a Single UK Paediatric Liver Transplantation Programme

Abstract: IntroductionPercutaneous transluminal angioplasty (PTA), with or without stent placement, has become the treatment of choice for portal vein complications (PVC) following liver transplantation. We aimed to assess long-term outcomes of intervention in paediatric transplant recipients, in a single institution.Materials and Methods227 children received 255 transplants between November 2000 and September 2016. 30 patients developed PVC of whom 21 had percutaneous intervention. Retrospective clinical and procedural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 29 publications
(41 reference statements)
0
23
0
Order By: Relevance
“…Only a few studies in our analysis exclusively reported primary patency for balloon angioplasty and stent placement in a Kaplan Meier format (see Table 4). These studies show that 1, 5 & 10 year primary patency rates of balloon angioplasty 20,23,24 were lower compared to primary stent groups 18,20 that showed 10 year patency at 100%. These results suggest that primary angioplasty is more likely to result in restenosis and require further interventions.…”
Section: Discussionmentioning
confidence: 79%
“…Only a few studies in our analysis exclusively reported primary patency for balloon angioplasty and stent placement in a Kaplan Meier format (see Table 4). These studies show that 1, 5 & 10 year primary patency rates of balloon angioplasty 20,23,24 were lower compared to primary stent groups 18,20 that showed 10 year patency at 100%. These results suggest that primary angioplasty is more likely to result in restenosis and require further interventions.…”
Section: Discussionmentioning
confidence: 79%
“…9 Fortunately, post-procedure angioplasty has been demonstrated to be effective in reducing the incidence of postoperative PVT. 26 HAT is associated with increased mortality, re-intervention, re-transplantation, and reduced long-term graft survival. 10,11,17,24,25 Although specific types of postoperative thrombotic complications were not defined in the UNOS database, the vast majority of these events in both adults and children are most likely related to HAT.…”
Section: Discussionmentioning
confidence: 99%
“…Stents with appropriate lengths to cover the stenosis with minimal angulation relative to the PV should be selected. In pediatrics, a balloon-expanding stent ≥ 7–8mm diameter and a short length is preferred because this type of stent can be positioned accurately, thus minimizing the difficulties of re-transplantation [ 22 23 ]. It can also be re-expanded or overdilated in the future if functional stenosis of the fixed stent occurs [ 24 25 ].…”
Section: Portal Vein Complicationsmentioning
confidence: 99%